SEQUENCE OF AILLIKITE AND CALCITE CARBONATITE FORMATION WITHIN THE BELAYA ZIMA MASSIF, EAST SIBERIA, RUSSIA - S. M. Zhmodik; I. V. Ashchepkov; D. K. Belyanin; E. V. Ayriyants; O. N. Kiseleva; V. A. Ponomarchuk (Геодинамика и тектонофизика, 2022)
The mineralogical and geochemical features, as well as the sequence of formation of aillikite and calcite carbonatite (CC) with pyrochlore are described for the massif of alkaline ultramafic carbonatite complexes Belaya Zima located in East Siberia. Until now, mutually exclusive information presents the temporal relationships of carbonatites and lamprophyres of the Belaya Zima massif.The sample marking the contact of aillikite and CC was comprehensive studied using analytical methods, e.g. XRF (ARL-9900XP spectrometer, ThermoFisher Scientific), ICP-MS (Element Finnigan MAT), SEM (MIRA 3 LMU (Tescan Ltd)), transmission and ore microscopy (AxioScope. A1, Zeiss), 40Ar/39Ar age determination of micas (Argus mass spectrometer, Micromass). The data obtained indicate a later formation of CC relative to aillikites and probable separation of the carbonatite melt from a single picrite-carbonatite source.